2012
DOI: 10.1073/pnas.1213423109
|View full text |Cite
|
Sign up to set email alerts
|

Epistasis dominates the genetic architecture of Drosophila quantitative traits

Abstract: Epistasis-nonlinear genetic interactions between polymorphic loci-is the genetic basis of canalization and speciation, and epistatic interactions can be used to infer genetic networks affecting quantitative traits. However, the role that epistasis plays in the genetic architecture of quantitative traits is controversial. Here, we compared the genetic architecture of three Drosophila life history traits in the sequenced inbred lines of the Drosophila melanogaster Genetic Reference Panel (DGRP) and a large outbr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
390
3

Year Published

2013
2013
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 353 publications
(413 citation statements)
references
References 27 publications
11
390
3
Order By: Relevance
“…Alternatively, part of the missing heritability may be caused by unknown loci that interact epistatically (Huang et al . 2012; Zuk et al . 2012), although the lack of epistasis among the loci we did detect suggests this may be less likely.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alternatively, part of the missing heritability may be caused by unknown loci that interact epistatically (Huang et al . 2012; Zuk et al . 2012), although the lack of epistasis among the loci we did detect suggests this may be less likely.…”
Section: Discussionmentioning
confidence: 99%
“…2014), widespread epistasis (Huang et al . 2012; Zuk et al . 2012; Mackay 2014), many very small effect loci (Yang et al .…”
Section: Introductionmentioning
confidence: 99%
“…A potential explanation lies in the highly polygenic nature of life‐history traits; it creates the opportunity for ample amount of nonadditive genetic variation—dominance, epistatic, and genotype‐by‐environment interactions (GEIs)—to exist. Recently, there have been studies quantifying dominance effects and epistasis (Armbruster, Bradshaw, & Holzapfel, 1997; Huang et al., 2012; Monnahan & Kelly, 2015), as well as the role of GEI in adaptation (e.g., Gutteling, Riksen, Bakker, & Kammenga, 2007; Jarosz & Lindquist, 2010; Rohner et al., 2013; for a review see Schlichting, 2008). Despite that, the pervasiveness of additive‐ and nonadditive variation—particularly for competitive traits—is still not yet well understood, especially in the context of environmental changes.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, quantitative genetics studies have often suggested that traits important to adaptation are polygenic, and quantitative trait loci (QTL) may have low repeatability between species (Arbuthnott, 2009;Huang et al, 2012;Rockman, 2012). One reason for this disparity may be that candidate genes are typically those that have a large influence on a particular trait, and thus the evolutionary forces affecting them are likely to be stronger and more consistent than those for smaller effect loci.…”
Section: Introductionmentioning
confidence: 99%